The comparison of perendoscopic injection therapy with medical treatment in Forrest’s II ulcers: Pilot study - Murat SARUÇ,; Feyzullah GÜÇLÜ,; Sabriye ÖZKAYA,; Nurten KÜÇÜKMETİN,; Hakan YÜCEYAR, (Turkish Journal of Gastroenterology, 2019)
-